Text Neck Syndrome: An Emerging Epidemic during COVID-19 Pandemic - Sigedar , Prakash; Giri, Purushottam (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Text neck syndrome has emerged as an epidemic during COVID-19 pandemic. Because of lockdown and work from home many young persons and school going students were working online and for long period. Due to long working hours and faulty neck postures, incidence of text neck syndrome is increasing especially in COVID-19 pandemic period. This article highlights this important public issue and gives insight about etiology, incidence, pathophysiology, symptoms and signs, treatment and prevention of text neck syndrome. It also gives comprehensive treatment approach for text neck syndrome including importance of life style modification, yoga, pranayam, reversal of modifiable risk factors etc. preventive aspect is given equal weightage with treatment in this article.